2010
DOI: 10.1007/s12221-010-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Model system for mechanistic study of catalytic bleaching of cotton

Abstract: We have dcveloped a homogeneous model system to study the mechanism of hydrogen peroxide bleaching using [Mn2O3(N,N'N ''-trimethyl-1-1,4,7-triazacyclononane)(2)](PF6)(2) (MnTMTACN) as catalyst. Thee primary model pigment exarnined is morin (3,5,7,2',4'-pentahydroxyflavone) owing to its presence in native cotton 1-iber. Additionally, a series of model compounds with systematic structural diffierences are examined in order to facilitate the development ofa mechanistic understanding of the bleaching system. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Morin is a flavonoid dye which is found in vegetables, fruits and in tea [27]. The oxidation of morin is used as a model reaction for catalytic bleaching in laundry detergents [28,29]. Manganese based systems have been reported to be efficient catalysts in the oxidation of morin [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morin is a flavonoid dye which is found in vegetables, fruits and in tea [27]. The oxidation of morin is used as a model reaction for catalytic bleaching in laundry detergents [28,29]. Manganese based systems have been reported to be efficient catalysts in the oxidation of morin [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of morin is used as a model reaction for catalytic bleaching in laundry detergents [28,29]. Manganese based systems have been reported to be efficient catalysts in the oxidation of morin [29][30][31]. In their study Gemeay et al [30] carried out a study on the oxidation of organic dyes, including morin, on polyaniline/MnO 2 composites using hydrogen peroxide as the oxidant.…”
Section: Introductionmentioning
confidence: 99%
“…The generated peracid has a higher oxidative potential and thereby allows bleaching to be conducted at low temperature [6]. Since the beginning of the 21 st century, a variety of bleach activators have been tested for use in activated peroxide systems, such as N- [4-(triethylammoniomethyl)benzoyl]-butyrolactam chloride (TBBC) [7], N- [4-(triethylammoniomethyl)benzoyl]lactam chlorides (TBLCs) [8], tetraacetylethylenediamine (TAED) [9], N- [4-(triethylammoniomethyl)benzoyl]caprolactam chloride (TBCC) [6], nonanoyloxybenzenesulfonate (NOBS) [10], [Mn 2 O 3 (N,N',N''-trimethyl-1,4,7-triazacyclononane) 2 ](PF 6 ) 2 (MnTMTACN) [11] and so on. Some reports have confirmed that TAED is one of the most effective activators.…”
Section: Introductionmentioning
confidence: 99%
“…Some attempts have been made to investigate new compounds as activators for H 2 O 2 bleaching systems to lower the bleaching temperature and shorten the reaction time without causing damage to the cellulose fibres. To date, only a few catalysts have met the requirements of retaining activity and stability under the alkaline conditions of cotton bleaching; these include the family of manganese coordination compounds with the ligand 1,4,7-trimethyl-1,4,7-triazacyclononane (TMTACN) [13][14][15][16][17]. Many other bleach activators have also been reported for the bleaching of cotton fabrics, such as guanidine derivatives [8] and TBCC {N-[4-(triethylammoniomethyl)benzoyl] butyrolactam chloride} [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%